2023
DOI: 10.2147/jaa.s430062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air Pollutants and Meteorological Factors on Daily Outpatient Visits of Allergic Rhinitis in Hohhot, China

Xue Wang,
Chenghua Gao,
Yuan Xia
et al.

Abstract: Objective There is limited evidence that atmospheric pollutants are associated with the number of allergic rhinitis (AR) visits. This study aimed to investigate the relationship between atmospheric pollutants and meteorological factors and the number of daily visits for AR in Hohhot City, providing a theoretical basis for further research on the effects of atmospheric pollutants on AR. Methods Microsoft Excel 2016 was used to collect and organize the AR outpatient consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Conversely, air pollutants such as O3, PM2.5, PM10, SO2, and NO2 were found to have a substantial impact on AR, according to a recent study in China that involved 12,868 instances of AR outpatients ( 58 ). A other study from 2023 found that there was a correlation between short-term exposure to PM2.5, PM10, SO2, NO2, and CO with an increase in AR clinic visits ( 59 ). This contentious matter can be explained by two primary factors.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, air pollutants such as O3, PM2.5, PM10, SO2, and NO2 were found to have a substantial impact on AR, according to a recent study in China that involved 12,868 instances of AR outpatients ( 58 ). A other study from 2023 found that there was a correlation between short-term exposure to PM2.5, PM10, SO2, NO2, and CO with an increase in AR clinic visits ( 59 ). This contentious matter can be explained by two primary factors.…”
Section: Discussionmentioning
confidence: 99%